Description of a new group of species of Edessa (Hemiptera: Pentatomidae: Edessinae) - Nascimento, Dariane Amorim Do; Mendonça, Maria Thayane Da Silva; Fernandes, Jose Antonio Marin (Zootaxa, 2017)
The new group of species viridula is proposed to five new species: Edessa viridula sp. n., Edessa exigusternata sp. n., Edessa angusticlada sp. n., Edessa rugulata sp. n. and Edessa eucnema sp. n. based on 58 specimens examined. Descriptions of the group and species are provided. Illustrations of the species along with metasternal process and male and female genitalia are provided; an identification key and distributional map are presented.